The Tools and Levers of Access to Patented Health Related Genetic Invention in Canada - S. Tina Piper (Washington University Journal of Law & Policy, 2009)
This Article argues that there is a prevailing problem of access to genetic invention in Canada caused by disputes over intellectual property rights arising from conflicting normative orders.
Keywords: Patents – Canada; Genetics; Health care industry – Canada; Health care industry – Law & amp; legislation; Gene therapy; Generic drugs; Health care services accessibility; Patent licensing; Bayh-Dole Act; Canada; United States